A systematic review and meta‐synthesis of qualitative studies on pelvic organ prolapse for the development of core outcome sets. Issue 3 (10th February 2020) - Rada, Maria Patricia; Jones, Stephanie; Falconi, Gabriele; Milhem Haddad, Jorge; Betschart, Cornelia; Pergialiotis, Vasilios; Doumouchtsis, Stergios K.
Abstract: Aims: In the current climate of evidence‐based health care, the aim of this meta‐synthesis was to collect and systematically analyse data from primary qualitative studies on pelvic organ prolapse (POP), to identify patient‐centered perspectives on the natural course of POP. Information acquired in this study may be useful for ongoing research towards the development of core outcome sets (COS) in pelvic floor disorders. Methods: A CHORUS Working Group performed a standardized search of three different databases (Medline, Embase, Scopus), from inception to October 2019. We selected qualitative studies on women's perspectives on POP that were published in the English language. Three reviewers independently evaluated the quality of eligible papers and highlighted recurrent themes based on patient perspectives. Results: Eighteen qualitative studies including a total of 497 patients were assessed in this analysis. Our study revealed five superordinate themes, recurrently encountered in qualitative studies on POP: awareness of POP (6 studies), communication (9 studies), treatments (10 studies), effects on quality of life (6 studies), and self‐image (3 studies). Five out of 10 quality criteria were met by all the studies included, based on an assessment performed using the critical appraisal skills program. Conclusions: This is the first synthesis of qualitative studies that address POP‐related experiences of women, highlighting five superordinate themes, of which treatment was the most commonly reported one. This synthesis' findings may guide quantitative research priorities and will hopefully contribute to the development of a COS for POP.